Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/hepr.13801
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization combined with lenvatinib versus transarterial chemoembolization combined with sorafenib for unresectable hepatocellular carcinoma: A comparative retrospective study

Abstract: Aim Tyrosine kinase inhibitors target transarterial chemoembolization (TACE)‐mediated vascular endothelial growth factor to inhibit tumor revascularization and to slow tumor progression. The present study aimed to compare the clinical outcomes of TACE combined with lenvatinib (TACE‐lenvatinib) and TACE combined with sorafenib (TACE‐sorafenib) in patients with unresectable hepatocellular carcinoma (HCC). Methods The clinical data of patients diagnosed with unresectable HCC who received TACE‐lenvatinib or TACE‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…The characteristics of the six enrolled studies are presented in Table 1. Among them, one study was a single-center prospective RCT from China (17), whereas the other five studies were single-center or multicenter prospective or retrospective cohort studies which were conducted in China, Japan and Korea (15,16,(18)(19)(20). A total of 598 patients with uHCC were included, of which 261 patients were treated with LEN+TACE combination therapy, whereas 337 patients were treated with SOR+TACE.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the six enrolled studies are presented in Table 1. Among them, one study was a single-center prospective RCT from China (17), whereas the other five studies were single-center or multicenter prospective or retrospective cohort studies which were conducted in China, Japan and Korea (15,16,(18)(19)(20). A total of 598 patients with uHCC were included, of which 261 patients were treated with LEN+TACE combination therapy, whereas 337 patients were treated with SOR+TACE.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition to sorafenib, other TKIs, including lenvatinib, regarofenib and cabozantinib, have been approved by the United States Food and Drug Administration (FDA) for the treatment of uHCC (14), and so a wide range of suitable combination treatment options are now available for patients. A comparative retrospective study (15) indicated that the median OS time was significantly longer in a lenvatinib plus TACE (LEN+TACE) treatment group compared with the sorafenib plus TACE (SOR+TACE) group (30.5 vs. 20.5 months; P = 0.018).…”
Section: Introductionmentioning
confidence: 99%
“… 33 Zhang et al found that the mOS of inoperable HCC patients receiving TACE-lenvatinib was 30.5 months. 34 In addition, Su et al confirmed that gamma knife radiosurgery has a superior OS compared to TACE in the treatment of PVTT-HCC. 35 Predicting the prognosis of HCC patients remains a formidable obstacle, despite the widespread use of numerous treatment methods in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…In the protocol, Sorafenib was pre-administered 2,3 weeks before TACE, and then Sorafenib was re-administered after TACE, and the endpoint was time to untreatable (unTACEable) progression. In recent years, LEN-TACE sequential therapy was reported to improve the prognosis of unresectable HCC in comparison to LEN alone, TACE alone, or TACE-SOR [ 13 , 14 , 15 , 16 , 17 ]. These reports differed from our study in the background of the HCC BCLC stage or the comparison of the treatment method (drug, TACE, etc.).…”
Section: Discussionmentioning
confidence: 99%